Design Efficient Vedic-Multiplier for Floating-Point MAC Module - Hussein, Fatima Tariq; AL-Assfor, Fatemah K. (Iraqi Journal for Electrical and Electronic Engineering, 2024)
Multiplication-accumulation (MAC) operation plays a crucial role in digital signal processing (DSP) applications, such as image convolution and filters, especially when performed on floating-point numbers to achieve high-level of accuracy. The performance of MAC module highly relies upon the performance of the multiplier utilized. This work offers a distinctive and efficient floating-point Vedic multiplier (VM) called adjusted-VM (AVM) to be utilized in MAC module to meet modern DSP demands. The proposed AVM is based on Urdhva-Tiryakbhyam-Sutra (UT-Sutra) approach and utilizes an enhanced design for the Brent-Kung carry-select adder (EBK-CSLA) to generate the final product. A (6*6)-bit AVM is designed first, then, it is extended to design (12*12)-bit AVM which in turns, utilized to design (24*24)-bit AVM. Moreover, the pipelining concept is used to optimize the speed of the offered (24*24)-bit AVM design. The proposed (24*24)-bit AVM can be used to achieve efficient multiplication for mantissa part in binary single-precision (BSP) floating-point MAC module. The proposed AVM architectures are modeled in VHDL, simulated, and synthesized by Xilinx-ISE14.7 tool using several FPGA families. The implementation results demonstrated a noticeable reduction in delay and area occupation by 33.16% and 42.42%, respectively compared with the most recent existing unpipelined design, and a reduction in delay of 44.78% compared with the existing pipelined design.